Pola keperluan penyeliaan guru bimbingan dan kaunseling sepenuh masa di Sekolah Menengah Malaysia - Abd. Ghani, Faizah (2007)
This study examined the developmental level and the pattern of supervisory needs of full time counselors in Malaysia Secondary Schools. The Ex Post Facto design was used and the theoretical framework of this study was based on The Stoltenberg Supervisory Model and The Bernard Discrimination Model. A total of 226 randomly selected subjects responded, yielding a 82.9% respond rate. Three sets of questionnaires namely Developmental Level Questionnaire, Emphasis on Job Questionnaire and Supervisor Role Questionnaire designed by the researcher were used in this study. The questionnaire for measuring Developmental Level showed alpha Cronbach of 0.749 for dependent level, 0.779 for conflict level, 0.766 for confident level and 0.703 for expert level. The questionnaire for Emphasis on Job showed alpha Cronbach of 0.800 for academic, 0.660 for career, 0.809 for psychosocial and mental health, 0.639 for education on drug and HIV/AIDS prevention. The questionnaire for Supervisor Role showed alpha Cronbach of 0.802 for teachers, 0.759 for counselors and 0.806 for consultants. The descriptive analysis of data showed that 65.9% respondents were at the confident level followed by the dependent (22.6%), expert (10.6%) and conflict level (.9%). In the area of preferred supervisory emphasis, the respondents ranked professional behaviour skills (37.6%) and followed by process skills (37.2%). The result also indicated that the psychosocial and mental health, parenting and education on drug and HIV/AIDS prevention were the important aspects needed to be focused by the supervisor. The study also showed that the respondents preferred counselor and consultant supervisory role by the full time counselors. One Way Anova analysis was used to compare the differences in supervisory emphasis, emphasis on job and preferred supervisor role based on the developmental level. It was found that in the supervisory emphasis, there were significant differences in conceptualization skills, professional behaviour skills and personalization skills. In the emphasis on job, the finding showed that there were significant differences in the aspects of parenting, education on drug and HIV/AIDS prevention. For the supervisor’s role, the results showed that there were significant differences in the role of teacher and counselor.